KINERJA REKSADANA SAHAM SYARIAH DAN REKSADANA SAHAM KONVENSIONAL - Lestari, Winda Rika (Jurnal Manajemen Magister Darmajaya, 2015)
Mutual Fund is one of investment instrument which grows recently together with the growth of Indonesia stock market. In the growing, mutual fund starts to set Syariah principal in doing of its business. The main difference between Syariah mutual fund and conventional mutual fund is at the investment policy and the investorâs type. The aim of this study is to know whether there is a difference between Syariah mutual fund performance and conventional mutual fund. The population in this study is the mutual fund which is managed by Investment manager who manages the two sub Syariah mutual fund category and stock type conventional. Analysis method uses comparative method and average difference test by using independent sample t-test method through SPSS and Sharpe method to decide the best stock mutual fund rank. The research result shows that conventional stock mutual fund performance is better than Syariah stock mutual fund performance based on Sharpe method as 11.900, while based on independent sample t-test is proved that there is a significant difference between Syariah stock mutual fund performance and conventional stock mutual fund performance through the significance score as 0,012 > 0,05Key Words : Conventional Mutual Fund, Syariah Mutual Fund, Sharpe Method.